PENGARUH PENAMBAHAN TEPUNG JAHE MERAH (Zingiber officinale var Rubrum) DALAM PAKAN AYAM BROILER TERHADAP PERTAMBAHAN BOBOT BADAN, KONVERSI PAKAN DAN KONSUMSI PAKAN - Fitria Sekar Ningsih; Novi Eka wati; Miki Suhadi (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2021)
ABSTRACT This aim of study was to determined effect of red ginger flour (Zingiber Officinale Var Rubrum) as herbal feed additive in Broiler Chiken on feed comsumption, daily body weight gain and feed conversion ratio.The research was conducted on September – Oktober 2020 at Gisting Atas Village, Gisting District, Tanggamus Regency, Lampung. The experiment used 80 unisex Broiler aged 1 week. They were feed a ration with control ration + 0% red ginger flour (P0), control ration + 0,25% red ginger flour (P1), control ration + 0,5% red ginger flour (P2), control ratio + 0,75% red ginger flour (P3) during 20 days. The control ration containing 21% crude protein and 3108 kkal/kg metabolism energy. The study used a quantitative methods with completely randomized design with 4 treatments and 4 replications. The results showed that the ration had no effect (P> 0,05) on feed comsumption, daily weight gain and conversion ratio. The conclution of the research showed that the addition of level red ginger flour (Zingiber Officinale Var Rubru) until 0,75% as herbal feed additive in Broiler Chiken no effect on feed comsumption, daily body weight gain and feed conversion ratio. Keywords: Red ginger flour, Broiler, Feed Comsumption, Daily Weight Gain, Feed Conversion Ratio.